A study on relationship between E-resources awareness and reading habits of research papers among Research scholars in selected Universities in Andhra Pradesh. - • Dr.K.Geetanjali, Patrini. Dhanalakshmi, Vennela. Appala Naidu, Dr. K. Lakshmi Sirisha, Dr. P. Jayalakshmi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The objective of this research work is to determine the relationship between the level of awareness regarding E-resources and reading habits of research papers among the research scholars in selected state Universities in Andhra Pradesh. This paper also aims to highlight the relationship between e-resources awareness and reading habits of research papers among research scholars. Knowledge acquiring and research are essential for sustaining a developed economy, elevating social needs and inspiring a country to reach new heights in the globe. Education and research, at any time of life span are helpful to provide overall wellness and growth. Research paper reading is an integral part of the research process. By regular approach or habit to reading research papers, academics can improve their existing knowledge and improve their overall understanding capacity of a subject. This study is based on primary and secondary data. This study applied the statistical methods and techniques are percentages, Mean, SD, T-Test and Correlation. The present reveals that the majority of the Research scholars of State universities in Andhra Pradesh both male and female have average level e-resources awareness and reading habits of research papers. Another finding reveals that male research scholars are better than female research scholars in their awareness of eresources. There is a significant difference between Government and Private Universities research scholars in their awareness as well as reading habits.